The Attitude of the Population To Tourism, The Impact Of Domestic Tourism On Women's Employment - Ashurov Bahtiyor Iskandarovich (Indonesian Journal of Innovation Studies, 2022)
This study examines whether the socio-demographics of the local population and public relations can influence their impact on tourism (economic, environmental and socio-cultural impacts), as well as their satisfaction with local tourism management. Checks the impact and prospects of tourism in the employment of the population in need of social protection, mainly women. At the same time, key issues leading to gender inequality will be discussed. According to a survey of local residents, attitudes towards tourism and the requirements of domestic tour packages were assessed.